2018
DOI: 10.1155/2018/1943497
|View full text |Cite
|
Sign up to set email alerts
|

Obesity-Related Asthma: Immune Regulation and Potential Targeted Therapies

Abstract: Obesity, one of the most severe public health problems of the 21st century, is a common metabolic syndrome due to excess body fat. The incidence and severity of obesity-related asthma have undergone a dramatic increase. Because obesity-related asthma is poorly controlled using conventional therapies, alternative and complementary therapies are urgently needed. Lipid metabolism may be abnormal in obesity-related asthma, and immune modulation therapies need to be investigated. Herein, we describe the immune regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 149 publications
0
13
0
2
Order By: Relevance
“…Association of asthma and obesity has been demonstrated in numerous epidemiological studies; however, the exact underlying mechanisms and detailed pathogenic link for this association are not well understood. A large number of factors are postulated including inflammation and immunometabolic dysregulation, [50][51][52][53][54] microbial dysbiosis, 55 mitochondrial dysfunction, 56 free fatty acid receptors, 57 glucagon-like peptide pathway, 58 and innate lymphoid cells (Fig 1). 28 It has been shown that obese asthmatic patients are characterized by a respiratory metabolic fingerprint fully different from that of patients independently affected by asthma or obesity.…”
Section: Mechanistic Studies (Human and Mouse) Detailed Metabolic Assessment: Immune-metabolic Interventionsmentioning
confidence: 99%
“…Association of asthma and obesity has been demonstrated in numerous epidemiological studies; however, the exact underlying mechanisms and detailed pathogenic link for this association are not well understood. A large number of factors are postulated including inflammation and immunometabolic dysregulation, [50][51][52][53][54] microbial dysbiosis, 55 mitochondrial dysfunction, 56 free fatty acid receptors, 57 glucagon-like peptide pathway, 58 and innate lymphoid cells (Fig 1). 28 It has been shown that obese asthmatic patients are characterized by a respiratory metabolic fingerprint fully different from that of patients independently affected by asthma or obesity.…”
Section: Mechanistic Studies (Human and Mouse) Detailed Metabolic Assessment: Immune-metabolic Interventionsmentioning
confidence: 99%
“…The multifactorial etiology of non-allergic asthma caused by obesity imposes an important limitation on the treatment of this disease. [34][35][36] The most important intervention is to prevent the disease in obese patients. Unfortunately, the general practitioner, pediatrician, and allergist do not currently have a biomarker that can predict non-allergic asthma in obese patients.…”
Section: Protocol and Laboratory Measurementsmentioning
confidence: 99%
“…The group of patients with BA on the background of obesity is not homogeneous. To date, two main phenotypes of the combination of asthma and obesity have been identified [1]: with an early onset of the disease, this is a variant of allergic asthma with an increase in type 2 T-helpers which is complicated by inflammatory processes in excess adipose tissue, and has a severe course of BA; with a late onset, this is a variant of non-atopic asthma, most often found in women, accompanied by less pronounced inflammation of the respiratory tract than the first variant, but characterized by significant General metabolic changes and manifestations of oxidative stress of the respiratory tract, the development of this type is also affected by chronic compression of the lungs caused by obesity of the chest walls [9,12].…”
Section: о заікіна клініко-лабораторні особливості хворих з коморбідністю бронхіальної астми та ожирінняmentioning
confidence: 99%
“…According to the latest report of the Global Initiative for Asthma (GINA) in 2021, the obesity asthma phenotype is associated with a severe course and difficulties in achieving control of symptoms with standard baseline therapy [4]. The comorbid course of asthma and obesity is accompanied by a greater number of symptoms, worse indicators of external respiratory function (RF) and quality of life, insufficient response to the control therapy of asthma compared with the isolated form of asthma [10,11], which in turn leads to an increase in the number of exacerbations of asthma and seeking medical help [9,12].…”
Section: о заікіна клініко-лабораторні особливості хворих з коморбідністю бронхіальної астми та ожирінняmentioning
confidence: 99%